2019
DOI: 10.1111/ecc.13118
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic management for taxane‐induced nail toxicity: A systematic review and meta‐analysis

Abstract: Objective This meta‐analysis was performed to assess the efficacy of cryotherapy and nail solution (NS) use in preventing nail toxicity (NT) induced by taxane‐based chemotherapy. Methods PubMed, EMBASE, Cochrane Library and ClinicalTrials.gov registry databases were searched for relevant studies published up to December 2018. The primary outcome was taxane‐induced NT. Secondary outcomes were skin toxicity (ST), time to toxicity and patient comfort. Results We reviewed three randomised control trials and six pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 32 publications
0
12
0
3
Order By: Relevance
“…Nail apparatus injuries are often painful and lead to the development of infections, while peripheral neuropathy may cause highly unpleasant sensory experiences, as in our patient, and sometimes also result in muscle weakness [11]. It has become a great challenge for dermatologists and oncologists to search for methods that prevent the development of nail apparatus changes and thus improve the quality of life of patients [12]. Peyton et al [11] suggested that cooling (a factor causing vasoconstriction, typically at temperatures in the range of -25°C to -30°C) of the toksycznego wpływu tej grupy leków na paznokcie u dwóch pacjentek chorujących na raka jajnika, u których zastosowano paklitaksel w połączeniu z cisplatyną.…”
Section: Opis Przypadkumentioning
confidence: 94%
See 3 more Smart Citations
“…Nail apparatus injuries are often painful and lead to the development of infections, while peripheral neuropathy may cause highly unpleasant sensory experiences, as in our patient, and sometimes also result in muscle weakness [11]. It has become a great challenge for dermatologists and oncologists to search for methods that prevent the development of nail apparatus changes and thus improve the quality of life of patients [12]. Peyton et al [11] suggested that cooling (a factor causing vasoconstriction, typically at temperatures in the range of -25°C to -30°C) of the toksycznego wpływu tej grupy leków na paznokcie u dwóch pacjentek chorujących na raka jajnika, u których zastosowano paklitaksel w połączeniu z cisplatyną.…”
Section: Opis Przypadkumentioning
confidence: 94%
“…Uszkodzenia aparatu paznokciowego często są bolesne i prowadzą do rozwoju infekcji, neuropatia obwodowa może powodować szczególnie nieprzyjemne dla chorych, podobnie jak u naszej pacjentki, zaburzenia czucia, a czasami także osłabienie siły mięśniowej [11]. Dużym wyzwaniem dla dermatologów i onkologów jest konieczność poszukiwania metod zapobiegania rozwojowi zmian aparatu paznokciowego, których zastosowanie poprawia komfort życia pacjentów [12]. Peyton i wsp.…”
Section: Opis Przypadkuunclassified
See 2 more Smart Citations
“…12 Many side effects such as cardiotoxicity, nail toxicity, peripheral neuropathy, fluid retention syndrome, arthralgia, myelosuppression, and skin reactions caused by taxanes have been identified. [13][14][15][16] In the literature, several case reports described the effect of taxanes on nails which includes onycholysis, melanonychia, subungal hemorrhage, subungual hyperkeratosis, Beau's lines, and nail dystrophy. 4,6,[17][18][19] In this work, we represent a clinical observational study to evaluate the effect of cosmetic nail lacquer on taxane-induced nail changes in female patients diagnosed with breast cancer.…”
Section: Introductionmentioning
confidence: 99%